MANAJEMEN PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI MADRASAH ALIYAH DARUNNAJAH 2 CIPINING BOGOR - Edi Santoso; Arizqi Ihsan Pratama; Musthafa Zahir (Bajang Institute, 2024)
This thesis discusses the management process for improving teacher pedagogical competence at Madrasah Aliyah Darunnajah 2 Cipining Bogor and what are the supporting and inhibiting factors. This type of this research is descriptive-qualitative research, with data collection methods through interviews, observation, and documentation. The data that has been obtained is then analyzed descriptively by data reduction, presentation, and data verification. The results of this study indicate that efforts to improve teacher pedagogical competence at Madrasah Aliyah Darunnajah 2 Cipining have gone well and are quite effective, planning is made based on an analysis of school needs, the principal works with the team he has made, the activities which been carried out are IHT, MGMP, ta'hil mudarrisin, and educational supervision, the evaluation is carried out at the end by holding teacher exams and distributing questionnaires. Supporting factors include: the number of education experts, the availability of facilities and infrastructure, the support and leadership of the school principal, relevants of communication media, and the awareness of each teacher. While the inhibiting factors include: the quick change of curriculum, many newbie teachers, a busy educational calendar, resistance to change, and low motivation.